(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
The aim of this work to study the effects of heat treatments on the alloy (Ti6Al4V) which produced by powder metallurgy methods and consists of a mixture of the following powders (titanium 90%, aluminum 6% and vanadium 4%).The heat treatments (sintering process) take place in different time of stay. The alloy (Ti6Al4V) used as biomaterials in the medical field due to their excellent properties such as : high corrosion resistance, high wear resistance, high breaking strength, higher ductility, non-toxic and non-magnetic, suitable elasticity coefficient, where used as an alternative to replacing damaged hard tissues such as orthopaedic, osteosynthesis, full hip joint, knee joint and dental implants. The elements were weighed by a highly sensitive electronic balance, the powder was mixed for five hours, Then press with a pressure (700 MPa) to transition to green cylindrical samples with a diameter of 13 mm. The sintering process was carried out at 1100 °C. The porosity of the samples decreases at high temperatures and time of stay to a certain extent and then increase porosity at very high temperatures due to the growth of particle and the expansion of gases. The density of the samples after the sintering process increases with increasing the temperature because increase the mass diffusion of particles and reduces porosities that increase contact points between particles. The sintering processes lead to increase the hardness, where the hardness was tested in the Vickers hardness method. The wear increased by increasing (load, time and sliding distance), and increase the hardness leads to a low volume loss (the amount of metal lost a few) as the relationship between them is inverse. To study the corrosion behavior of the samples that have been sintering processes under different time of stay and to perform this test (tafel Extrapolation test) in 0.9 NaCl solution, where the sample is subjected to high temperature and a long period of stay and therefore This lead to increases the diffusion and increases the contact points between the particles and increase the forces of bonds between the particles and this leads to increased corrosion current and therefore the oxidation process to be a high degree and this leads to the higher rate of corrosion.